Comparison of spatial transcriptomics technologies using tumor cryosections - Rademacher, Anne; Huseynov, Alik; Bortolomeazzi, Michele; Wille, Sina Jasmin; Schumacher, Sabrina; Sant, Pooja; Keitel, Denise; Okonechnikov, Konstantin; Ghasemi, David R.; Pajtler, Kristian Wilfried; Mallm, Jan-Philipp; Rippe, Karsten (Genome biology, 2025)
Spatial transcriptomics technologies are revolutionizing our understanding of intra-tumor heterogeneity and the tumor microenvironment by revealing single-cell molecular profiles within their spatial tissue context. The rapid development of spatial transcriptomics methods, each with unique characteristics, makes it challenging to select the most suitable technology for specific research objectives. Here, we compare four imaging-based approaches - RNAscope HiPlex, Molecular Cartography, Merscope, and Xenium - alongside Visium, a sequencing-based method. These technologies were employed to study cryosections of medulloblastoma with extensive nodularity (MBEN), a tumor chosen for its distinct microanatomical features.
Online erschienen: 20. Juni 2025
Gesehen am 08.12.2025